2019
DOI: 10.1001/jamanetworkopen.2019.8569
|View full text |Cite
|
Sign up to set email alerts
|

Primary Care Practices’ Ability to Report Electronic Clinical Quality Measures in the EvidenceNOW Southwest Initiative to Improve Heart Health

Abstract: Key Points Question How quickly can primary care practices report electronic clinical quality measures based on evidence-based guidelines for cardiac care? Findings In this quality improvement study of 211 primary care practices, the median time to report any baseline electronic clinical quality measure was 8.2 months. Time to report varied by measure type and practice characteristics. Meaning This study suggests that clinical qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…As of 2021, most (78.0%) office‐based physicians have adopted a certified EHR, suggesting that most offices have eCQM reporting capabilities 43 . However, emerging evidence suggests technical and implementation challenges may limit the utility of the eCQMs features 44,45 . For instance, studies in primary care have found that having eCQMs capabilities has not fully translated to efficient and timely reporting 44,45 .…”
Section: Discussionmentioning
confidence: 99%
“…As of 2021, most (78.0%) office‐based physicians have adopted a certified EHR, suggesting that most offices have eCQM reporting capabilities 43 . However, emerging evidence suggests technical and implementation challenges may limit the utility of the eCQMs features 44,45 . For instance, studies in primary care have found that having eCQMs capabilities has not fully translated to efficient and timely reporting 44,45 .…”
Section: Discussionmentioning
confidence: 99%
“…The study was further complicated by major changes in the cholesterol treatment guidelines just as the project was starting. Difficulties and delays with obtaining clean CQM data as reported elsewhere 57,58 made quality improvement efforts focused on specific measures problematic as well. Despite those barriers and limitations, practices improved all 4 of the ABCS measures significantly when compared with an external comparison group.…”
Section: Discussionmentioning
confidence: 99%
“…Reporting CQMs is difficult. 13 Practices not reporting CQMs over time were excluded because AUC requires multiple data points per practice; however, excluded practices may have been providing high-quality care to their patients. If further statistical analyses are required after practices are identified as exemplars, a sufficient number of practices will be needed in the exemplar group to conduct these analyses.…”
Section: Limitationsmentioning
confidence: 99%
“…[8][9][10][11] One of the funded cooperatives was EvidenceNOW Southwest, which aimed to improve the delivery of evidence-based guidelines in clinical practice in Colorado and New Mexico, using four cardiovascular care CQMs as one set of measures for evaluating outcomes. 12,13 Others have evaluated exemplary practices based on CQMs or colon cancer screening data using a single point in time. 6,14 The success of such pragmatic practice-based trials is often defined as the magnitude of improvement from baseline.…”
Section: Introductionmentioning
confidence: 99%